A design analysis method and its application in the cover arch of cut-and-cover tunnels - Zhang, Yong-Jie; Cao, Jun; Xu, Hong (Frontiers in Earth Science, 2023)
It is very important to improve the design of supports because the cut and cover method of layered backfill after construction is the primary method used to construct shallow buried sections of mountain tunnels. The Dujuan Valley Tunnel in Fenghua City is the subject of this research. First, a geometric model of a shallow buried section of a mountain tunnel and its construction parameters were used to develop the simplified bearing capacity analysis model for the covered arch. Second, a simplified method to calculate the internal force of the cover arch supporting structure was established by using the method of structural mechanics. Thus, a method was established to determine the safe thickness of the cover arch and to analyze the bearing capacity and stability of the enlarged foundation of the arch foot. Third, the influence of the tunnel burial depth, cap arch sag height, central angle, radius and arch foot width on the bearing characteristics of the cover arch support structure was discussed, and the optimal design principle of excavation in shallow buried sections of mountain tunnels was obtained. Finally, the calculation and evaluation of the design in an example case were used to determine the rationality of the method to design and optimize shallow buried sections of mountain tunnels with the cut and cover method.